2009
DOI: 10.1016/j.jmb.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

R992C (p.R1192C) Substitution in Collagen II Alters the Structure of Mutant Molecules and Induces the Unfolded Protein Response

Abstract: SummaryWe investigated the molecular bases of spondyloepiphyseal dysplasia (SED) associated with the R992C (p.R1192C) substitution in collagen II. At the protein level we analyzed the structure and integrity of mutant molecules, and at the cellular level we specifically studied the effects of the presence of the R992C collagen II on the biological processes taking place in host cells. Our studies demonstrated that mutant collagen II molecules were characterized by altered electrophoretic mobility, relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 42 publications
(62 reference statements)
2
65
0
Order By: Relevance
“…The unfolded protein stress response (UPR) has been implicated in OA progression. We and others have reported that collagen mutant mouse strains Dmm, Cho and Sedc exhibit distended ER and Golgi, consistent with the mis-folded type II collagen being trapped in the ER rather than secreted to the extracellular matrix [15,16]. We have previously reported a 1.66 fold increase in BiP expression in Dmm/+ newborn articular cartilage compared to wild type (p = 0.01).…”
supporting
confidence: 74%
“…The unfolded protein stress response (UPR) has been implicated in OA progression. We and others have reported that collagen mutant mouse strains Dmm, Cho and Sedc exhibit distended ER and Golgi, consistent with the mis-folded type II collagen being trapped in the ER rather than secreted to the extracellular matrix [15,16]. We have previously reported a 1.66 fold increase in BiP expression in Dmm/+ newborn articular cartilage compared to wild type (p = 0.01).…”
supporting
confidence: 74%
“…, Fabry’s and Gaucher’s diseases (Yam et al 2006; Maor et al 2013; Ron et al 2010); and in the pathology of diseases involving professional secretory tissues such as cystic fibrosis and α1-antitrypsin deficiency (Bartoszewski et al 2011; Alam et al 2014). Recent reports investigating effects of mutations on assembly and secretion of several ECM components suggest that multiple outcomes such as misfolding and intracellular accumulation of mutant ECM proteins may result from induction of ER stress (Chung et al 2009; Liang et al 2014; Rajpar et al 2009; Pieri et al 2014; Firtina et al 2009; Gould et al 2007; Nugent et al 2009; Bateman et al 2009; Boot-Handford and Briggs 2010; Yang et al 2005). …”
Section: Endoplasmic Reticulum Stress and The Diseasesmentioning
confidence: 99%
“…Although individually rare, they cause a significant impact on the quality of life for patients suffering from skeletal abnormalities. Genes encoding cartilage ECM proteins affected by mutations which disrupt growth plate differentiation comprise collagen types II, IX, X, and XI; aggrecan; cartilage oligomeric matrix protein (COMP); and matrilin 3 (Hintze et al 2008; Chung et al 2009; Liang et al 2014; Ho et al 2007; Mäkitie et al 2010; Kuivaniemi et al 1997; Warman et al 2011; Bateman et al 2009; Boot-Handford and Briggs 2010; Yang et al 2005; Briggs et al 2015). The list of collagenopathies associated with mutations in collagen types II and X is presented in Table 1.…”
Section: Mutations Leading To Cartilage Pathologymentioning
confidence: 99%
See 2 more Smart Citations